Costa Rica: reference soils in the Atlantic Coastal Region under forest and pasture. Soil Brief Costa Rica 1 - Veldkamp, E.; International Soil Reference and Information Centre, Wageningen (Países Bajos); Weitz, A.M. (CATIE, Turrialba (Costa Rica) International Soil Reference and Information Centre, Wageningen (Países Bajos), 2014)
21 pág, 17 ilus, 12 ref.